2008
DOI: 10.1177/0022466908323008
|View full text |Cite
|
Sign up to set email alerts
|

Generalizability Theory Applied to Reading Assessments for Students With Significant Cognitive Disabilities

Abstract: Students with significant disabilities must participate in large-scale assessments, often using an alternate assessment judged against alternate achievement standards. The development and administration of this type of assessment must necessarily balance meaningful participation with accurate measurement. In this study, generalizability theory is used to estimate the dependability of reading items and tasks that have been administered using two formats of communication (receptive and expressive). The results r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 29 publications
0
11
0
1
Order By: Relevance
“…In addition, implementation of these supports has been shown to not compromise the reliability of the test. In a study by Tindal, Yovanoff, and Gellar (2010), generalizability theory analyses suggested that the test administrator was a negligible facet in the reliability of the test. These results and the Tindal et al results suggest that well-defined administrator-provided supports in standardized, performance-based alternate assessments can help students access the test while not compromising reliability and the validity of test-based inferences.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, implementation of these supports has been shown to not compromise the reliability of the test. In a study by Tindal, Yovanoff, and Gellar (2010), generalizability theory analyses suggested that the test administrator was a negligible facet in the reliability of the test. These results and the Tindal et al results suggest that well-defined administrator-provided supports in standardized, performance-based alternate assessments can help students access the test while not compromising reliability and the validity of test-based inferences.…”
Section: Discussionmentioning
confidence: 99%
“…While perfect agreement and kappa analyses have been used to measure rater agreement and reliability for classroom and teacher observations, generalizability and decision studies are able to account for variability that traditional interrater agreement analyses cannot (Brennan, 2001; Cronbach et al, 1972; Hill, Charalambous, Blazar, et al, 2012; Tindal, Yovanoff, & Geller, 2010). The use of generalizability theory, or G theory, to inform the use of the RESET tool is important because it accounts for multiple sources of variance that cannot be measured in interrater agreement analyses like kappa, and reflects a much more realistic measurement of what happens in a classroom.…”
Section: Generalizability Theorymentioning
confidence: 99%
“…Additional analyses were completed to test the hypothesis of administration format on measurement reliability. Using generalizability theory (Brennan, 2000; Yovanoff, Tindal, & Geller, 2010), reliability was estimated by computing the systematic variation due to students, format, and occasions, and the interaction of these sources of variability. While student true score variability is desirable, other sources of variability are regarded as systematic and random “error” (attributable to sources such as occasions, format, student).…”
Section: Methodsmentioning
confidence: 99%